Productivity and quality of potato cultivars for processing as shoestrings and chips - Araújo,Thaís H (2016)
ABSTRACT Brazilian market of potato processing has presented expressive development in recent years. However, its expansion is constrained by raw material supply suitable for industrial processing. Selection of adequate cultivars contributes to final product cost reduction as well as its yield and quality improvement. The research aimed to study tuber yield and evaluate its frying potential for shoestrings and chips, of potato cultivars recently introduced in Brazil. Nine potato cultivars (Arizona, Caruso, Destiny, Excelence, Saviola, Agata, Almera, Fontane and Markies) were assessed in an experiment carried out between January and May, 2013, in South-West region of Minas Gerais State, Brazil. 'Arizona' and 'Caruso' cultivars exhibited superior productive potential and along with 'Markies' the highest production of marketable tubers. 'Caruso' and 'Destiny' produced more than 20% of dry matter and the lowest reducing sugar levels. 'Caruso' exhibited the highest frying yield in both processing shapes and absorbed less fat as shoestring. 'Destiny' absorbed less fat when processed as chips. 'Excelence' presented intermediary performance for every evaluated attribute. 'Caruso', 'Destiny', and 'Excelence' produced chips with appropriate color for market. Among the assessed cultivars, 'Caruso', 'Destiny', and 'Excelence' were the most promising. These cultivars demonstrated appropriate processing ability in the shape of shoestrings. 'Destiny' could also be indicated to be processed as chips.